Producción investigativa en estudiantes de la Facultad Nacional de Salud Pública de la Universidad de Antioquia en el período 2004-2008 (2011)
ABSTRACT: To describe the research production of undergraduate students from the National Faculty of Public Health (Facultad Nacional de Salud Pública, FNSP), Universidad de Antioquia, during the period 2004-2008. Methods: descriptive study document review. The Study population was limited to graduation projects according to their different modalities (research projects, development project and monographs) of the three undergraduate programs at the FNSP and research papers published in the Revista Facultad Nacional de SaludPública during the period 2004-2008. The analysis unit was restricted to graduation projects that could be located at the FNSP library and research papers including undergraduate students as authors. Descriptive statistics were used for the analysis of the data collected. Results: a total amount of 279 graduation projects were reviewed, from wich 119 (42.7%) were research projects. In the undergraduate program of Management of Health Information Systems, research projects were the most frequent type of graduation project (79.1%). This proportion was smaller in the health administration programs both in its emphasis in health services (36.2%) and in its emphasis on environment and sanitation (19.7%). A total amount of 126 research papers were reviewd finding 22 (17.5%) with undergraduate students of the FNSP as coauthors. The proportion of research projects published in the Revista FNSP was 11.8%. Conclusions: during the period 2004-2008, two out of five graduation projects in the FNSP were research projects. During the period studied important differences according to the undergraduate programs were observed. The proportion of research projects published in the Revista FNSP is still very small.